The influence of a series of ten sauna baths on hematological biomarkers and changes of plasma volume following a submaximal exercise test in elite athletes - Pokora, I.; Wolowski, L.; Kempa, K. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: It is known that numerous conditions, including environment, exercise and training, can affect changes in plasma volume. These modulations pose a particular problem when trying to determine the consequences of incorporating regular sauna bathing into the training process of elite athletes. Elite athletes often have developed certain thermal adaptations as a result of their long-term training history, which may limit the effectiveness of thermal interventions (HA), such as plasma volume increases, or greatly hinder the ability to identify the beneficial effects of HA on the body. The purpose of this study was to examine the effects of a series of ten sauna baths on selected hematological biomarkers and changes of plasma volume following a submaximal exercise test in elite athletes.